PERBANDINGAN PENDEKATAN PEMBELAJARAN TCL DAN SCL TERHADAP PEMAHAMAN MATA DIKLAT PERATURAN PERUNDANGAN PERTAMBANGAN - Mirna Mariana (PPSDM Geominerba, 2020)
The research was conducted to compare Teacher Center Learning (TCL) and Student Center Learning (SCL) approaches for better understanding in Mining Regulation especially Safety and Environment Regulation. The research method used is qualitative with descriptive analysis method, directional discussion, and question – answer the lesson plan in SCL approach are used Small Group Discussion, Contextual Instruction, and Problem Based Learning methods. The observation results from a comparison between the two learning approaches, the results show that the SCL approach provides an understanding result of 76% being able to understand and apply legislation, while the TCL approach is only 31%. The results of the questionnaire illustrate that the SCL approach gives more confidence to participate in implementing K3 and environmental legislation with a satisfaction index of 3.23 (almost achieving very good).